Formulation of polymer composite from starch/PVA and crosslinking with silica from rice husk ash for polymer flooding - Mohd Yunan, Muhammad Afiq Iqmal; Kassim Shaari, Norin Zamiah (Universiti Teknologi MARA Shah Alam, 2025)
This research project focuses on the creation of a polymer composite by combining potato starch, polyvinyl alcohol (PVA), and silica from rice husk ash (RHA) for polymer flooding in enhanced oil recovery (EOR). This study aims to overcome the limitations of the polymer use for EOR, such as polymer degradation, shear-thinning behaviour, and viscosity control of the polymer. The polymer blend of starch/PVA was crosslinked with silica from RHA, which is expected to enhance the shear-thinning behaviour and control the viscosity of polymer solutions. The investigation involves varying silica concentration to observe its impact on shear rate and viscosity. The methodology includes the extraction of silica from rice husk and the preparation of the polymer composite solution, followed by characterisation of the polymer using Fourier Transform Infrared Analysis and viscosity analysis. The polymer composite was expected to withstand the harsh conditions in the reservoir, which can help to enhance the oil recovery. The polymer composites showed stability in viscosity as the temperature rose, indicating high thermal stability, with no effects from the salinity in 2.5% and 5% saline concentration. In conclusion, the presence of silica, particularly 3%, can improve the rheological properties of biopolymer solutions, making them more stable under reservoir conditions such as high salinity and temperature.